Pengaruh Minat Mahasiswa Terhadap Tabungan Wadiah Pada Bank Syariah di Kota Malang - Ahmad Zakqi Dinal Falakh; Afifudin Afifudin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to analyze and determine the effect of student interest on wadiah savings at Islamic banks in the city of Malang. This type of research is descriptive rather than quantitative. Sampling was carried out using the Slovin formula. There are 100 respondents from Malang City students who use the wadiah savings account of Bank Syariah Indonesia. The analytical tool used is simple linear regression using SPSS. The results showed that the student interest variable (X1) had a positive and significant effect on using wadiah savings (Y) in Indonesian Islamic banks in Malang City.Â